2000
DOI: 10.1023/a:1007629920752
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study confirms a female excess of symptom reporting and utilization of medical services. Nevertheless, symptom reporting and utilization are not closely related. The gender gap in symptom reporting may be largely explained by low social class status, high levels of chronic distress and poor perceived/self assessed health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(79 citation statements)
references
References 24 publications
6
68
2
Order By: Relevance
“…It was also found that no age and sex specific pattern on healthcare expenditure exists in Bangladesh (Figure 1) which also similar with the findings of other studies (Gómez 2002; Ladwig et al 2000). A number of studies observed that sex and reproductive biology and mortality to male–female differences in the use of health care services, which also reflected in the current study (Mustard et al 1998; Roos et al 1987).…”
Section: Discussionsupporting
confidence: 89%
“…It was also found that no age and sex specific pattern on healthcare expenditure exists in Bangladesh (Figure 1) which also similar with the findings of other studies (Gómez 2002; Ladwig et al 2000). A number of studies observed that sex and reproductive biology and mortality to male–female differences in the use of health care services, which also reflected in the current study (Mustard et al 1998; Roos et al 1987).…”
Section: Discussionsupporting
confidence: 89%
“…This confirms and extends the gender difference reported in previous studies that did not focus solely on chronic symptoms 45 7 8 38 In contrast, Hellström et al 39 did not report any gender difference in the number of symptoms. In their study, Ladwig et al 7 suggest that the gender gap may be mediated by a lower socioeconomic status and higher levels of chronic distress in women.…”
Section: Discussionsupporting
confidence: 87%
“…26,30,33 In addition, women were more likely to seek the health services in PHC institutions because of low socioeconomic status. 34 Second, the proportion of low- and middle-income groups was 63.70%. This study indicated that they were more likely to utilize the health care services.…”
Section: Discussionmentioning
confidence: 95%